GIS tools for water, wastewater, and stormwater systems - Shamsi, Uzair M. (Reston, Virginia ASCE Press, 2002)
Data and software are the two most important tools for developing GIS applications. This book focuses on GIS data and software for water, wastewater, and stormwater systems. With appropriate GIS data and software, the possible means to manage water, wastewater, and stormwater systems are almost endless. This book is intended as a reference book on GIS data and software for water, wastewater, and stormwater system applications. It is suitable for any professional involved in the management and operation of water, wastewater, and stormwater systems.
Keywords: Geographic information systems; Sewerage -- Data processing; Waterworks -- Data processing; Electronic books